VERHOEVEN’S GIANT RAT OF FLORES, INDONESIA (Papagomys theodorverhoeveni Musser, 1981; Muridae) IS A MODERN SPECIES A. Suyanto, C. H.S. Watts 10.14203/treubia.v32i1.592 - Suyanto , A.; Watts , C. H. S. (Treubia, 2015)
The giant rat of Flares, Papagomys armandvillei (Jentink, 1892) lives in small remnants of relatively undisturbed forest on the island of Flores, Eastern Indonesia. It is a rare animal but in recent years specimens have been collected from Ruteng, Manggarai, (Ruteng is the capital of district Manggarai) West Flores. It appears to be most abundant (or most easily obtained) in the area around Ruteng in West Flares. Within museum collections it is represented by 13 specimens, the vast majority collected prior to 1970. From the locality records of 13 specimens the species is, or was, distributed in Potjong, Sika, Mboera, Ruteng, Manggarai, Nunang and Wewo Pongkor, Flores, Indonesia. It is also presented as subfossils of recent age from Liang Toge, a cave near Warukia, 1 km south of Lepa, in Manggarai District (ill printed as Menggarai Province), Western Flores (Musser, 1981). Also present in this deposit are the fragmentary remains of a closely related species of giant rat which has been described as Papagomys theodorverhoeveni by Musser (1981). This material consisted of 18 mandibular fragments with either partial or intack tooth rows (Hooijer, 1957, Musser 1981). We record here a modem specimen among other 4 specimens of Papagomys armandvillei collected after 1970, unfortunately represented only by skull and mandibles that was discovered in the collections of the Museum Zoologicum Bogoriense (MZB) during a check following the transfer of the mammals (and other zoological collections) from the Bogor Botanical Garden to new modem building at Cibinong, 23 km north of Bogor City.